CURRENT STATUS OF TREATMENT ADHERENCE AND RELATED FACTORS AMONG OUTPATIENTS WITH CHRONIC DISEASES IN THU DUC CITY 2024-2025 - Khoa Lý, Nguyễn; Thị Bích Uyên, Nguyễn; Thị Vân Anh, Trương; Thanh Hương, Lâm; Thị Liên, Phạm (Journal of Health and Aging, 2026)
To describe the current status of treatment adherence among outpatients with chronic diseases and to analyze factors associated with treatment adherence in Thu Duc City during 2024–2025. Cross-sectional descriptive study. The study included 253 patients with hypertension, 150 patients with diabetes mellitus, and 130 patients with chronic obstructive pulmonary disease (COPD) treated at Le Van Viet Hospital and Thu Duc City Medical Center (Facilities 1, 2, and 3) from July 2024 to March 2025. The mean age was 65.7 ± 10.9 years; 52.2% were male and 47.8% were female. The duration of illness was 6.8 ± 6.5 years. Hypertension and diabetes were mostly discovered incidentally; 74.6% of COPD patients were diagnosed when symptoms appeared. 10% of hypertensive patients, 17.3% of diabetic patients, and 6.2% of COPD patients had at least one comorbidity. 67.7% of hypertensive patients had blood pressure
Keywords: Chronic disease; treatment adherence; regular check-ups